Atypical Pyoderma gangrenosum: a case of delayed recognition - Anum Qureshi; Kia Persaud; Sajida Zulfiqar; Ranadheer Dande; Chahat Puri; Shankar Awasthi (Greater Baltimore Medical Center, 2021)
Pyoderma gangrenosum (PG) is an inflammatory skin condition that is often misdiagnosed as a necrotizing infection. This diagnosis must be considered in any patient with underlying systemic disease who presents with large ulcerating lesions that are unresponsive to antibiotics. Early diagnosis and a multidisciplinary approach to treatment are crucial to achieving improvement in quality of life and minimizing cosmetic morbidity.